Pengaruh Pendidikan, Pelatihan Dan Pengembangan Karir Terhadap Kinerja Pegawai - Ai Elis Karlinda; Putri Intan Permata Sari; Tri Ayu Parwati (CV. ITTC INDONESIA, 2025)
This study aims to determine how much, the influence of education, training and career development on employee performance at the Padang City Regional Drinking Water Company. Data collection methods through questionnaires and literature studies. The analysis method used is multiple regression analysis. The results of the study obtained based on partial tests (t-tests) obtained: (a) Education has a significant effect on Employee Performance. (b) Training has a significant effect on Employee Performance. (c) Career Development has a significant effect on Employee Performance. (d) Education, Training and Career Development together have a significant effect on Employee Performance. Finally, the author suggests to the Padang City Regional Drinking Water Company (PDAM) to be able to improve Education, Training and Career Development by using the indicators contained in this study.